Integrated Review to Combat Food Loss and Waste in Maritime Southeast Asia: A Short Literature - Vioni Derosya; Taufiq Ihsan (Jurnal Serambi Engineering, 2025)
Food loss and waste (FLW) is a global issue with profound implications for food security, environmental sustainability, and economic systems. This problem is particularly acute in Maritime Southeast Asia, where individual contributions to FLW can exceed 150 kilograms per year. Despite its significance, applied research on the underlying causes, management strategies, measurement methodologies, and policy frameworks for FLW mitigation in this densely populated region (over 400 million people) is conspicuously lacking. Our comprehensive literature review identified only 15 articles directly relevant to the topic, offering a limited perspective on the complexities of FLW generation. The methodologies employed in these studies lack the robustness required for wider application within the region or for broader comparative analyses. The review, therefore, requires urgent, expansive research across the entire food supply chain in Maritime Southeast Asia and considers factors such as the social, technological, behavioral, and cultural, further elucidating what the real causes and drivers of FLW are within the region.